The acceptability of asking women to delay removal of a long-acting reversible contraceptive to take part in a preconception weight loss programme: a mixed methods study using qualitative and routine data (Plan-it) - Susan Channon; Elinor Coulman; Rebecca Cannings-John; Josie Henley; Mandy Lau; Fiona Lugg-Widger; Heather Strange; Freya Davies; Julia Sanders; Caroline Scherf; Zoe Couzens; Leah Morantz (BMC, 2022)
Abstract Background Having a body mass index (BMI) which is classified as overweight (BMI ≥ 25) or obese (BMI ≥ 30) increases the risk of complications during pregnancy and labour. Weight-management interventions which target excess gestational weight gain during pregnancy have had limited success. Women who use long-acting reversible contraception (LARC) are in contact with services as part of their preparation for conception, creating a potential opportunity to offer a preconception weight-loss intervention. The aims of this mixed methods study were to assess the acceptability and practicability of a weight-loss intervention which asked people to delay LARC removal in order to lose weight before conceiving. Methods Routine UK NHS data were analysed to identify pathways from LARC removal to pregnancy. Qualitative surveys and advisory group discussions with service providers and LARC users with experience of being overweight were conducted and analysed thematically. Results Three hundred fifteen thousand seven hundred fifty-five UK women aged 16-48 years between 2009-2018 had at least one LARC-related event (e.g. insertion, removal) and 1.7% of those events were recorded as related to planning a pregnancy. BMI was included in 62% of women's records, with 54% of those BMI being classified as overweight or obese. Online surveys were completed by 100 healthcare practitioners and 243 LARC users. Stakeholders identified facilitators and barriers associated with the proposed intervention including sensitivities of discussing weight, service-user past experiences, practitioner skills, the setting and ethical implications of the proposed intervention. Conclusions Although women and service providers recognised potential benefits, a preconception weight-loss intervention asking people to delay LARC removal posed many barriers, due mainly to the acceptability of such an intervention to women and healthcare practitioners. Weight-loss interventions that target the general population, together with a focus on improving public knowledge of preconception health, may be more acceptable than interventions which solely focus on LARC users. Many of the barriers identified, including communication, understanding and beliefs about weight and risk, appointment systems and the limitations of routine datasets also have relevance for any preconception weight-loss intervention. Work to improve routine datasets and reducing communication barriers to discussing weight are priorities. Trial registration ISRCTN14733020 registered 10.05.2019.